2014
DOI: 10.1002/cncr.28739
|View full text |Cite
|
Sign up to set email alerts
|

Physical, emotional, and social health differences between posttreatment young adults with cancer and matched healthy controls

Abstract: PURPOSE Young adults (YAs; ages 18–39) with cancer face interrupted developmental milestones and increased stressors that can adversely influence psychosocial adjustment. Transitioning from active treatment to post-treatment survivorship can be particularly challenging. The purpose of this study is to describe the health-related quality of life (HRQL) and psychological adaptation of YAs post-treatment relative to young adults without cancer. METHODS Three cohorts of YAs of mixed cancer diagnoses (N=120, 0–12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 36 publications
(65 reference statements)
1
98
0
Order By: Relevance
“…26 Other cohorts of AYA’s that were much larger (between N=300 and N=6000) found that AYA’s reported more distress than controls. 2729 These inconsistent findings may be due to differing populations of survivors, methodologies or measures used.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
“…26 Other cohorts of AYA’s that were much larger (between N=300 and N=6000) found that AYA’s reported more distress than controls. 2729 These inconsistent findings may be due to differing populations of survivors, methodologies or measures used.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
“…Concerns about the achievement of life goals may be especially distressing for adolescents and young adult survivors [4,5], who are negotiating greater autonomy across life domains and are motivated to achieve future goals. Adjustment to challenged goals constitutes adaptive self-regulation [7] and may be particularly critical when cancer occurs in early adulthood [8,9]. Understanding the skills young adult cancer survivors need to navigate challenges to their goals may help facilitate adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Young adult cancer survivors are a population of particular clinical interest because they have been found to be particularly susceptible to psychological adjustment problems after cancer, with several studies demonstrating higher rates of anxiety and depression compared to same-age peers (Hobbie et al, 2000; Kwak et al, 2013a; 2013b; Michel, Rebholz, von der Weid, Bergstraesser, & Kuehni, 2010; Recklitis et al, 2010; Salsman et al, 2014; Zeltzer et al, 2009). Psychological screening has been recommended to address this risk in YACS (Children's Oncology Group, 2013; Clinton-McHarg et al, 2010; Langeveld, Stam, Grootenhuis, & Last, 2002; Recklitis, O'Leary, & Diller, 2003), but there is limited empirical information to guide selection of screening measures for this population.…”
mentioning
confidence: 99%